2005
DOI: 10.1385/mb:29:1:11
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Clone Sequence Confirmation Using a Mismatch-Specific DNA Endonuclease

Abstract: Site-directed mutagenesis and polymerase chain reaction (PCR)-based cloning are well-established methods carried out routinely in most modern molecular biology laboratories. Application of these methods requires confirmation of the DNA sequence of the target gene by sequencing of DNA purified from multiple colonies, a laborious process. We have developed an alternative approach to screen DNA amplified directly from colony DNA for both desired and undesired mutations. This approach is based on the use of a plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…2). Qiu et al also reported that mismatch cleavage preferences fall into four groups from the most favorite CT, AC, and CC to the least preferred AA, GG, and finally followed by the least favorable AG and GT [23]. Given that for every substitution, two types of heteroduplexes are produced; in almost all cases at least one of the two heteroduplexes formed is an ideal substrate for the endonuclease.…”
Section: Discussionmentioning
confidence: 99%
“…2). Qiu et al also reported that mismatch cleavage preferences fall into four groups from the most favorite CT, AC, and CC to the least preferred AA, GG, and finally followed by the least favorable AG and GT [23]. Given that for every substitution, two types of heteroduplexes are produced; in almost all cases at least one of the two heteroduplexes formed is an ideal substrate for the endonuclease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, many papers refer to SURVEYOR as a very efficient method for mutation detection in human (see below) as well as non-human 5,6 genes for screening of induced point mutations (TILLING) in several organisms, [7][8][9] for detecting heteroplasmy, 10,11 and for clone sequence validation. 12 Its application to human genetic disorders resulted in the discovery and description of many novel mutations in genes such as BRCA1, 1,2,13 EGFR, 14 JAK2, 15 hCDC4, 16 ATRX, 17 mitochondrial genes, 10,11 ABCC6, 18 p53, 19 NPHS2, 20 TP53, 21 COL4A3, and COL4A4. 22 There are advantages of SURVEYOR compared with other traditional mutation detection methods like singlestrand conformation polymorphism analysis, denaturing high-performance liquid chromatography, and heteroduplex analysis.…”
mentioning
confidence: 99%
“…[12][13][14] It has been used to accurately detect various mutations in human, mammalian, bacterial, and plant genomes. [15][16][17][18] The study developed a new, highly sensitive, and costeffective method for identifying and enriching mutant DNA. Using this method, we genotyped two majorities of activating mutations in lung cancer that occur in EGFR and KRAS genes.…”
Section: Introductionmentioning
confidence: 99%